Harlequin fetus: A case report - Mangesh Machindra Londhe; Tushar Vitthalrao Patil; Kishor Hiraman Suryawanshi (Wolters Kluwer Medknow Publications, 2022)
Harlequin ichthyosis (HI) is the most severe type of congenital ichthyosis. It is extremely rare with very few cases reported in India. It is inherited in an autosomal recessive fashion. The importance of antenatal diagnosis by ultrasonography, DNA-based molecular studies on chorionic villus sampling, and amniocentesis has been emphasized. We report a new case of HI in an infant, diagnosed postnatally by correlation of clinical and histopathological features on skin biopsy. The infant succumbed on the second day of birth despite intensive supportive care. A short review of the literature regarding the condition is also presented.